خريطة حقل من العصر السومري الحديث في متحف السليمانية - كامل ئاري خليل (مجلة دراسات في التاريخ والآثار, 2024)
The text here presented belong to the small collection acquired, in the ‎recent years, by Süleymaniah museum, located in Kurdistan, Iraq, which includes an ‎unpublished tablet dating from the third dynasty of Ur.‎ The tablet has suffered significant damage. It is a Field Plan used in ‎agriculture for a family in the Category of Land Tenure.